Kinematic Analysis of Performance of World Class Javelin Thrower - Sharma, Biswajit; Mukhopadhyay, Kishore (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2022)
The purpose of the study. Charles Darwin’s concept of the struggle for existence is now converted into a struggle for excellence. The ancient spear and hunting in now converted popular athletic sporting events in the form of javelin throw. Science plays a major role in maximizing the javelin throw's horizontal distance. Tremendous research indicates the various kinematic parameters and their role in better performance. The present analytical study discusses the trends of research in javelin performance and their successful implementation in the actual sporting field. The purpose of the study is to compare the different research findings for better javelin performance on kinematic parameters and analysis of biomechanical parameters such as height, weight, BMI, and performance of the last ten Olympic gold medals holders both male and female javelin throwers. Materials and methods. The meta-analysis was done based on other researchers' research findings. The correlation matrix has been calculated on height, weight, BMI, and performance of ten male and ten female Olympic gold medalists in the javelin throw. Results. The male and female throwers were positively correlated in height and weight and male throwers were negatively correlated in BMI and height. Conclusions. Based on the findings of other researchers the meta-analysis on kinematic parameters was discussed and it indicated that javelin performance is related to the biomechanical aspect of sports and height and weight are positively related for the throwers.